Analisis Dinamika Organisasi pada PT Tanikota Agribudaya Edulestari - Sihombing, Debora; Sukayat, Yayat (Universitas Galuh, 2024)
PT Tanikota Agribudaya Edulestari is a company engaged in urban agriculture. Despite diversifying its business and applying technology, the company as a whole has not yet achieved profitability. The purpose of this study is to identify and analyze the obstacles faced by the company in running its business using an organizational approach. This study examines the elements of group dynamics, including group goals, group task functions, group cohesion, group development and maintenance, group structure, group atmosphere, group pressure, and group effectiveness. The research method used is qualitative with descriptive analysis. The results of the study indicate that out of 32 sub-variables, 10 sub-variables align with the indicators of organizational dynamics, while the other 22 sub-variables do not. The sub-variables that do not align include: the meaning of organizational goals, member orientation towards the organization, the balance of tasks and activities towards goal achievement, conflict resolution related to organizational goals, the level of coordination between members, decision-making authority, coordination, information, initiative, satisfaction, clear task division, organizational activities, member participation, the organizational socialization process, member addition activities, interaction among members, personal interaction, the atmosphere within the organization, competition among members, recognition, goal achievement activities, and internal organizational maintenance activities. This indicates that the organizational dynamics within the company still face challenges in conducting business operations.